Associations Between Mode of Birth and Neuropsychological Development in Children Aged 4 Years: Results from a Birth Cohort Study - Takács, Lea; Putnam, Samuel P; Monk, Catherine; Dahlen, Hannah G; Thornton, Charlene; Bartoš, František; Topalidou, Anastasia; Peters, Lilian L (Child psychiatry and human development, 2021)
The aim of this prospective longitudinal study was to examine the association between Cesarean section (CS) and child development and behavior. The sample consisted of 256 children who were born at term without serious perinatal pathologies. Their development and behavior was assessed at the age of four using Ages and Stages Questionnaire (ASQ-3), Children's Behavior Questionnaire and Strength and Difficulties Questionnaire. Multivariate linear regression analyses were conducted to assess the association between CS and child outcomes. CS was associated with better scores in the Problem Solving domain of the ASQ in the whole sample. After stratifying by child sex, the positive association between CS and the Problem Solving domain was significant in boys, while no association was found in girls. Girls were rated less optimally in the Gross Motor domain of the ASQ when born via CS. Mode of birth was not associated with behavioral outcomes.
Keywords: Male; kohortové studie; Child Development; longitudinální studie; vývoj dítěte; Cohort Studies; Child; Pregnancy; těhotenství; dítě; Prospective Studies; mužské pohlaví; Cesarean Section; lidé; ženské pohlaví; Humans; Longitudinal Studies; Female; císařský řez; prospektivní studie